Microorganisms in the ticks Amblyomma dissimile Koch 1844 and Amblyomma rotundatum Koch 1844 collected from snakes in Brazil. Issue 1 (28th November 2018) - Ogrzewalska, M.; Machado, C.; Rozental, T.; Forneas, D.; Cunha, L. E.; de Lemos, E. R. S.
Abstract: Knowledge about ticks (Acari) and screening of ticks parasitizing various hosts are necessary to understand the epidemiology of tick‐borne pathogens. The objective of this study was to investigate tick infestations on snakes (Reptilia: Squamata: Serpentes) arriving at the serpentarium at the Institute Vital Brazil, Rio de Janeiro. Some of the identified ticks were individually tested for the presence of bacteria of the genera Rickettsia (Rickettsiales: Rickettsiaceae), Borrelia (Spirochaetales: Spirochaetaceae), Coxiella (Legionellales: Coxiellaceae), Bartonella (Rhizobiales: Bartonellaceae), Ehrlichia (Rickettsiales: Anaplasmataceae), Anaplasma (Rickettsiales: Anaplasmataceae), and Apicomplexa protozoa of the genera Babesia (Piroplasmida: Babesiidae) and Hepatozoon (Eucoccidiorida: Hepatozoidae). A total of 115 hard ticks (Ixodida: Ixodidae) were collected from 17 host individuals obtained from four Brazilian states. Two species of tick were identified: Amblyomma dissimile Koch 1844 (four larvae, 16 nymphs, 40 adults), and Amblyomma rotundatum Koch 1844 (12 nymphs, 43 adults). Rickettsia bellii was found in A. rotundatum and A. dissimile ticks and Rickettsia sp. strain Colombianensi, Anaplasma ‐like and Hepatozoon sp. in A. dissimile ticks. Among the tested ticks, no DNA of Borrelia, Bartonella, Coxiella or Babesia was found. The present findings extend the geographic range of Rickettsia sp. strain Colombianensi in Brazil and provide novel tick–host associations. Abstract : Two species of tick were collected from snakes in Brazil: Amblyomma dissimile Koch 1844 and Amblyomma rotundatum Koch 1844. Rickettsia bellii was found in A. rotundatum and A. dissimile ticks, and Rickettsia sp. strain Colombianensi, Anaplasma ‐like and Hepatozoon sp. in A. dissimile ticks. No DNA of Borrelia, Bartonella, Coxiella or Babesia was found in the tested ticks.